Abstract ID: 77 Monte Carlo simulation of the Elekta VersaHD linac with Elekta's Stereotactic Conical Collimation System. (October 2017) - Borzov, E.; Nevelsky, A.; Bar-Deroma, R.; Orion, I.
Abstract : Purpose: Small field dosimetry remains a challenging task. The difficulties associated with small fields measurements become more pronounced for field sizes less than 1 cm. To overcome these difficulties it has been suggested to employ Monte Carlo (MC) techniques. The purpose of this work was to report the results of commissioning and MC validation of the new Elekta stereotactic conical collimator system for 6 MV flattening filter free (FFF) beams on Elekta VersaHD linac. Methods: Commissioning measurements for stereotactic cones with diameters of 5 mm, 7.5 mm, 10 mm, 12.5 mm and 15 mm included relative output factor (ROF), percentage depth dose (PDD) and off-axis ratio (OAR) measurements and were performed with SRS diode. MC simulations were performed using EGSnrc. The incident electron beam parameters were adjusted to match the measured data (PDD and OAR) for set of MLC-based open fields. For each cone, aperture size was adjusted to match MC calculated and measured OAR profiles. Penumbra width (defined as 20%–80% distance) comparison of MLC-based and cone-based fields for a static angle case and for a full arc was performed. Angular distribution of photons collimated with MLC and with the cones was calculated. Leakage for the MLC and for the cones was determined. Results: For MLC-based fields, agreement between calculated and measured values was within 1%/0.5 mm for PDDs, within 1%/1 mm for OARs, and within 3% for ROFs. For stereotactic cones, the agreement in PDD and OAR profiles was within 1%/0.5 mm and the ROFs agreed within 3%. The measured ROFs were 0.564, 0.645, 0.706, 0740 and 0.770 for the 5 mm, 7.5 mm, 10 mm, 12.5 mm and 15 mm cones, respectively. For one static MLC-based 1 × 1 cm field, penumbra was 5.6 mm in the in-plane direction and 8.4 mm in the cross-plane direction, compared to 4 mm in both directions for the 10 mm cone. The cone leakage was found to be 0.5% for both energies. Conclusions: Results of our MC calculations were found to be in good agreement with the measurements thus confirming accuracy of our MC model for the Agility MLC.